MVP: a microbe-phage interaction database - Gao, Na L.; Bork, Peer (Nucleic acids research, 2018)
Abstract. Phages invade microbes, accomplish host lysis and are of vital importance in shaping the community structure of environmental microbiota. More import
Published online 21 November 2017
Gesehen am 25.09.2019